PENGARUH MODEL PEMBELAJARAN MAKE A MATCH BERBANTUAN MEDIA KARTU GAMBAR TERHADAP MOTIVASI BELAJAR SISWA KELAS V SD NEGERI 008 PALEMBANG - Leonardo Davinsi; Erma Yulaini; Budi Utomo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of students learning motivation caused by the use of conventional teaching methods at SD Negeri 008 Palembang. The purpose of this study was to determine the effect of the Make a Match learning model assisted by picture card media on the learning motivation of fifth-grade students at SD Negeri 008 Palembang. This study employed a Quasi-Experimental Design. The population consisted of all fifth-grade students at SD Negeri 008 Palembang. A saturated sampling technique was used, resulting in a sample of 27 fifth-grade students. Data were collected through observation, questionnaires, and documentation. The data analysis techniques included observation data analysis, questionnaire data analysis, normality testing, homogeneity testing, simple linear regression analysis, coefficient of determination analysis, and hypothesis testing. The results of the study showed that the average observation score was 78.77%, while the average questionnaire score increased from 57.63% before the treatment to 73.63% after the treatment, indicating an improvement in students learning motivation. The hypothesis testing revealed that the calculated t-value (t = 10.968) was greater than the critical t-value (t = 2.059), indicating that the hypothesis was accepted. These findings demonstrate that the Make a Match learning model assisted by picture card media has a significant effect on the learning motivation of fifth-grade students at SD Negeri 008 Palembang. Therefore, the Make a Match learning model assisted by picture card media, particularly in teaching the topic My Biodiverse Indonesia on the diversity of Indonesian flora and fauna, is recommended for implementation in fifth-grade classrooms at SD Negeri 008 Palembang, because this has been shown to influence students learning motivation while simultaneously creating an active and enjoyable learning environment